Conflict Between Local Leagues in District Expansion in Central Sulawesi: Case Study in Banggai Islands and Parigi Moutong - Haliadi, Haliadi; Najamuddin, Lukman; Windayanti, Windayanti (MUHARRIK: Jurnal Dakwah dan Sosial, 2024)
This research aims to outline the process of prosecuting expansion as a demand for regional autonomy in Banggai Islands Regency and Parigi Moutong Regency, explaining the comparison of horizontal and vertical conflicts in the implementation of regional autonomy in Banggai Islands Regency and Parigi Moutong Regency, and analyzing the involvement of local figures in expansion and conflict resolution in Banggai Regency Parigi Moutong Islands and Regency. This research uses historical methodology by collecting (heuristics), source criticism, and classifying and analyzing various social problems in the conflict and molibu culture of the Kaili community, Central Sulawesi. This research analysis uses a case study approach. The theories used in analyzing the results of this research are decentralization theory, regional autonomy and conflict theory. The research stages use historical methodology with four essential stages: heuristics, source criticism, interpretation, and historiography. The results of the research found that the conflict that occurred in Banggai Islands Regency was a conflict over the placement of the capital city, which should have been in Banggai City and then moved to Salakan Peling Island, while in Parigi Moutong Regency, it was a structural conflict in the Donggala Regency DPRD with the Gempar Parigi Moutong Group.